CCR5-ligand decorated rilpivirine lipid-based nanoparticles for sustained antiretroviral responses - Milankumar Patel; Sudipta Panja; Lubaba A. Zaman; Pravin Yeapuri; Shaurav Bhattarai; Santhi Gorantla; Linda Chang; Alonso Heredia; Piotr Walczak; Brandon Hanson; Samuel M. Cohen; Bhavesh D. Kevadiya; et al. (Nature Communications)
Abstract Antiretroviral therapy (ART) improves the quality of life for those living with the human immunodeficiency virus type one (HIV-1). However, poor compliance reduces ART effectiveness and leads to immune compromise, viral mutations, and disease co-morbidities. Here we develop a drug formulation in which a lipid-based nanoparticle (LBNP) carrying rilpivirine (RPV) is decorated with the C-C chemokine receptor type 5 (CCR5) targeting peptide. This facilitates extended drug persistence within myeloid cells. Particle delivery to viral reservoirs is tracked by positron emission tomography. The CCR5-mediated LBNP cell uptake and retention reduce HIV-1 replication in human monocyte-derived macrophages and infected humanized mice (hu mice). Focused ultrasound with microbubbles mediated blood brain barrier (BBB) disruption allows the CCR5-targeted LBNP to penetrate the BBB and reach brain myeloid cells. These findings offer a role for CCR5-targeted therapeutics in antiretroviral delivery to optimize HIV suppression.